2017
DOI: 10.1055/s-0037-1599155
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Testing in Burn Patients

Abstract: Severe burn injury has an impact on the coagulation system, but a unique definition regarding these changes is still missing. The results of conventional coagulation assays (CCAs) measured in daily clinical practice are often interpreted as coagulopathic, which implies a bleeding tendency. However, viscoelastic coagulation assays (VCA) like Rotational Thromboelastometry (ROTEM) and Thromboelastography (TEG) depict a hypercoagulable state. Therefore, hemostatic interventions should not be indicated according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…The ROTEM investigations included a regular extrinsically activated (EXTEM) assay, which was conducted as per the manufacturer’s instructions to detect extrinsically activated clotting dynamics [ 13 , 14 ]. In addition, we used two modified assays known to correlate with anti-Xa levels in vitro: low-tissue-factor (low-TF) and prothrombinase-induced clotting time (PiCT) ROTEM [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROTEM investigations included a regular extrinsically activated (EXTEM) assay, which was conducted as per the manufacturer’s instructions to detect extrinsically activated clotting dynamics [ 13 , 14 ]. In addition, we used two modified assays known to correlate with anti-Xa levels in vitro: low-tissue-factor (low-TF) and prothrombinase-induced clotting time (PiCT) ROTEM [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The linear regressions in Figure 2 revealed that clot initiation did not correlate with anti-Xa trough levels in the modified PiCT (rho = 0.11; p = 0.29) and low-TF (rho = 0.01; p = 0.88) assays throughout the four examinations at baseline and on days A to C of hemodialysis. and by two modified assays of low-TF (low-tissue-factor) ROTEM and PiCT (prothrombinase-induced clotting) NATEM (i.e., non-activated ROTEM) known to correlate greatly with anti-Xa levels [14]. Median values for the four examinations are connected by horizontal lines, with vertical lines extending from the 1st to 3rd The area highlighted in gray indicates the only available reference range (for CT by EXTEM).…”
Section: Rotem Parameters During Crrtmentioning
confidence: 99%
“…In addition, five microsurgical revisions were required because of arterial thrombosis (7%), venous insufficiency (14%), or hematoma (14%). Routine rotational thromboelastometry (ROTEM) during preoperative evaluation showed hypercoagulopathy in ten patients (71%) consistent with a hypercoagulative state that is described as beginning 48 h after trauma [ 20 , 35 , 36 ]. All documented operative revisions and flap loss occurred in patients with altered coagulation and nearly all complications occurred in patients with a delay of 19 to 30 days between burn trauma and defect reconstruction.…”
Section: Outcome and Complicationsmentioning
confidence: 99%
“…3,32 What has emerged in recent years is that it is no longer sufficient to rely solely on plasmatic prothrombin time, international normalized ratio, or activated partial thromboplastin time to diagnose coagulopathy and guide treatment. 3,[33][34][35][36][37] Other trauma trials suggest that similar limitations may also apply to relying exclusively on single point parameters from viscoelastic methods (e.g., clot times and indices of clot lysis). [38][39][40] Fig .…”
Section: Trauma-induced Coagulopathy: a Bewildering Heterogeneitymentioning
confidence: 99%